2015
DOI: 10.1017/hpl.2014.50
|View full text |Cite
|
Sign up to set email alerts
|

Temperature dependence of parametric instabilities in the context of the shock-ignition approach to inertial confinement fusion

Abstract: The role of the coronal electron plasma temperature for shock-ignition conditions is analysed with respect to the dominant parametric processes: stimulated Brillouin scattering, stimulated Raman scattering, two-plasmon decay (TPD), Langmuir decay instability (LDI) and cavitation. TPD instability and cavitation are sensitive to the electron temperature. At the same time the reflectivity and high-energy electron production are strongly affected. For low plasma temperatures the LDI plays a dominant role in the TP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
21
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 69 publications
(120 reference statements)
6
21
0
Order By: Relevance
“…In previous small-scale-length PIC simulations [4,5,7], pump depletion through convective SRS and SBS in the low density region was not significant, due to the small lengths. The long-scale-length simulations here show that the convective modes can lead to significant pump depletion before the quarter-critical surface and an accurate assessment of this requires control of the seed levels in simulations.…”
Section: Discussion and Summarymentioning
confidence: 77%
See 1 more Smart Citation
“…In previous small-scale-length PIC simulations [4,5,7], pump depletion through convective SRS and SBS in the low density region was not significant, due to the small lengths. The long-scale-length simulations here show that the convective modes can lead to significant pump depletion before the quarter-critical surface and an accurate assessment of this requires control of the seed levels in simulations.…”
Section: Discussion and Summarymentioning
confidence: 77%
“…In this high laser intensity regime, growth rates of many laser plasma instabilities (LPI) exceed their thresholds, such as the two plasmon decay (TPD), the stimulated Raman scattering (SRS), and the stimulated Brillouin scattering (SBS). Previous Particle-in-Cell (PIC) simulations showed large laser reflectivities at high intensities due to SBS and SRS [3,4], saturation of TPD due to plasma cavity formation [5], intermittent LPI activities due to interplay of modes at different density regions [6], and LPI's dependence on plasma temperatures [7]. Both the integrated SI experiment on OMEGA [8] and the PIC simulation [6] showed that the LPI generated hot electrons with a temperature of ∼ 30 keV.…”
Section: Introductionmentioning
confidence: 96%
“…151.22(a), is in the SRS-dominated regime: the threshold for SRS is exceeded by a factor of +22, while the TPD threshold is exceeded by a factor of +6. It is expected that this qualitative trend of SRS being increasingly prominent relative to TPD with increasing scale length and temperature 32 applies also for more-complicated cases of multiple obliquely incident beams, although this is a subject of future work. This observation is attributed to SRS sidescatter, 33 for which newly developed theory and supporting simulations are described in a companion manuscript.…”
Section: Origins and Scaling Of Hot-electron Preheat In Ignition-scalmentioning
confidence: 96%
“…These processes are important as they determine also the hot electron production. Depending on their distribution function they might be beneficial for driving shocks or detrimental as they can induce preheat of the compressed fuel (two recent reviews consider in some details parametric processes for ICF using kinetic simulations [23,24] and detailed references therein).…”
Section: Warm Dense Mattermentioning
confidence: 99%